2005
DOI: 10.1071/aj04029
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Potential of the Ceduna Sub-Basin: Impact of Gnarlyknots–1a

Abstract: The Ceduna Sub-basin, located in the eastern Bight Basin, is one of the few frontier deepwater provinces in Australia whose hydrocarbon potential remains largely untested. The sediments of the sub-basin span an area of over 95,000 km2—comparable to the combined area of the Exmouth, Barrow and Dampier sub-basins on Australia’s North West Shelf. Prior to 2003, exploration wells had been drilled only on the present day shelf area of the sub-basin. The recent Gnarlyknots–1A well, drilled in May 2003 by the Woodsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Schofield and Totterdell (2008) reported that in the central Ceduna sub-basin, sills and dykes are typically intruded at various levels in the late Santonian-Maastrichtian Hammerhead Supersequence, implying a post-Maastrichtian age for these intrusions. The Hammerhead Supersequence encompasses the Potoroo Formation, which contains fluvio-deltaic sandstones that exhibit excellent reservoir potential and were the target of the Potoroo-1 and Gnarlyknots-1 wells (Tapley et al, 2005).…”
Section: Bight Basinmentioning
confidence: 99%
“…Schofield and Totterdell (2008) reported that in the central Ceduna sub-basin, sills and dykes are typically intruded at various levels in the late Santonian-Maastrichtian Hammerhead Supersequence, implying a post-Maastrichtian age for these intrusions. The Hammerhead Supersequence encompasses the Potoroo Formation, which contains fluvio-deltaic sandstones that exhibit excellent reservoir potential and were the target of the Potoroo-1 and Gnarlyknots-1 wells (Tapley et al, 2005).…”
Section: Bight Basinmentioning
confidence: 99%
“…These segments mostly deviate from the general NW-SE orientation of the curvilinear Mulgara Fault Family (Fig. 1, Totterdell and Bradshaw, 2004;Tapley et al, 2005) and show a more E-W strike orientation (Fig. 6).…”
Section: Central Ceduna Sub-basinmentioning
confidence: 93%
“…The fault-related mounds in the central Ceduna Sub-basin are located over the present-day oil-mature area for the Santonian Tiger and the Cenomanian Upper White Pointer supersequences (Fig. 10, Tapley et al, 2005;Totterdell et al, 2008).…”
Section: Relationship Between Mound Complexes and Source Rocksmentioning
confidence: 98%
See 2 more Smart Citations